The Effect of Nonlinear Frequency Compression on Acoustic Change Complex Responses in High-Frequency Dead-Regioned Hearing Loss - (:unkn) unknown (THIEME MEDICAL PUBL INC, 2021)
Purpose The study is concern with the distinguishing of the stimuli containing high frequency information with the frequency compression feature at the cortical level using the acoustic change complex (ACC) and the comparison of such with the ACC answers of individuals with normal hearing. Research Design This is a case-control study. Study Sample Thirty adults (21 males and nine females) with normal hearing, ranging in age between 16 and 63 years (mean: 36.712.9 years) and 20 adults (16 males and four females) with hearing loss ranging in age between 16 and 70 years (mean:49.019.8 years) have been included in this study. Data Collection and Analysis A total of 1,000ms long stimulus containing 500 and 4,000Hz tonal stimuli was used for ACC recording. The start frequency (SF) and compression ratio (CR) parameters of the hearing aids were programmed according to the default settings (SFd, CRd) in the device software, the optimal setting (SFo, CRo), and the extra compression (SFe, CRe) requirements and ACC has been recorded for each condition. Evaluation has been performed according to P1-N1-P2 wave complex and ACC complex wave latencies. Independent samples t -test was used to test the significance of the differences between the groups. Results In all individuals ACC has been observed. There was a significant difference between the wave latencies in normal hearing- and hearing-impaired groups. All wave latency averages of the individuals with hearing impairment were longer than the individuals with normal hearing. There were statistically significant differences between SFd-SFo, SFd-SFe, and SFo-SFe parameters. But there was no difference between CRd, CRo, and CRe in terms of CRs. Conclusion In order to discriminate high frequency information at the cortical level we should not rely on default settings of the SF and CR of the hearing aids. Optimal bandwidth must be adjusted without performing insufficient compression or over-compression. ACC can be used besides the real ear measurement for hearing aid fitting.
Keywords: frequency lowering; nonlinear frequency compression; acoustic change complex; dead region; SPEECH-PERCEPTION; EVOKED-POTENTIALS; CHILDREN; DISCRIMINATION; SPECTRUM